Ответы и решения

Решите уравнение (7x+3)-(5x-7)=(2x-5)-(3x-6); 3(2x-3)+4(2-5x)=7(2-3x)-2(3x-2)​

+293 голосов
919k просмотров

Решите уравнение (7x+3)-(5x-7)=(2x-5)-(3x-6); 3(2x-3)+4(2-5x)=7(2-3x)-2(3x-2)​


Математика (55 баллов) | 919k просмотров
Дан 1 ответ
+114 голосов

1. (7х+3)-(5х-7)=(2х-5)-(3х-6)

7х+3-5х+7=2х-5-3х+6

7х+3х-5х-2х=6-5-3-7

3х= -9

х= -9:3

х= -3

2. 3(2x-3)+4(2-5x)=7(2-3x)-2(3x-2)​

6х-9+8-20х=14-21х-6х+4

6х+6х+21х-20х=9+4+14-8

13х=19

х= 19:13

х= 1целая6/19

Начинающий (669 баллов)
10,984,878 вопросов
13,471,016 ответов
8,518,553 комментариев
4,909,216 пользователей